TINGKAT KECEMASAN SISWA KELAS IX SMP PGRI 2 DENPASAR PADA MARET 2015 DALAM MENGHADAPI UJIAN NASIONAL 2012 - Dewi Larasati Apsari Susila; Wayan Westa (DiscoverSys Inc., 2015)
National exam is used as a standardization of the government to test a feasibility of student to be able to continue their education to a higher level and as a national educational equity. National exam is often used as a load by the students. This disturbing their psychological anxiety that would interfere with their activities as a threat nature. Tranquility in the conduct of national examinations is absolutely necessary for the students of junior high schoolPGRI 2 so that early detection of anxiety levels of students needs to be done. This research is quantitative descriptive cross sectional descriptive design was conducted on March 22, 2015 in Junior high schoolPGRI 2. These samples were taken with stratified random sampling technique and obtained 90 samples that met the inclusion criteria of exclusion. Data was collected using TMAS (Taylor Manifest Axientas Scale). The results found 57.1% of women have a mild anxiety, 55.1% moderate and 80% anxiety severe anxiety. And men found mild anxiety 42.9%, 44.9 % anxiety moderate, 20% severe anxiety. Students who follow the guidance of learning found 42.9% had mild anxiety, anxiety was 44.9%, 46.7% severe anxiety. So it can be said women have a tendency to experience anxiety than men and students who follow the guidance of learning tend to have lower levels of anxiety. Conclusion, research must be done in order to find a solution to anxiety levels were found in student.Â